Hard coating film and resin molded article using same
By using fluorine-containing leveling agents and other ingredients in the hard coating, the problem of taking into account the leveling and recoating properties of hard coating films when improving surface hardness and abrasion resistance is achieved, and efficient hard coating film design is achieved , suitable for multi-layer stacking applications.
Patent Information
- Application Number
- CN202380044942.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-20
- Filing Date
- 2023-07-10
- Publication Date
- 2025-01-14
AI Technical Summary
While improving surface hard coatings, it is difficult to take into account both leveling and recoating properties, which often leads to coating depression and unevenness.
By using fluorine-containing leveling agent in the hard coating, the fluorine atom concentration and surface roughness are controlled, and combined with photopolymerization initiator, polyurethane acrylate and inorganic particles, a hard coating film structure with high smoothness and good recoating properties is formed. .
It realizes a hard coat film with high surface hardness, excellent abrasion resistance, good leveling and recoating properties, and is suitable for multi-layer laminate applications, such as anti-reflective films for displays.
Smart Images

Figure BDA0005169531260000191
Abstract
Description
Technical Field
[0001] The present invention relates to a hard coating film having a substrate layer and a hard coating layer, and a resin molded product using the hard coating film. The present invention particularly relates to a hard coating film having high surface hardness, excellent scratch resistance, and excellent leveling (smoothness) and recoatability (re-coating property). Background Art
[0002] In recent years, substrate films, especially biaxially oriented polyester films, have been used in various fields such as magnetic recording materials, packaging materials, electrical insulation materials, optical display materials (such as anti-reflection films, touch screen films), etc. due to their excellent performance in mechanical properties, dimensional stability, heat resistance, transparency and electrical insulation.
[0003] Although the above-mentioned substrate films have gradually been used as substitutes for glass products from the perspectives of light weight and processability, these substrate films have the disadvantage that the surface is easily damaged. Therefore, in order to impart scratch resistance, a hard coating is usually provided or a film provided with a hard coating is attached before use. In addition, in existing glass products, in order to prevent scattering caused by glass breakage, plastic films are often attached before use, and forming a hard coating on the surface is a widely used method.
[0004] However, in the above-mentioned existing hard coatings, in order to improve the smoothness of the coating film after curing, a leveling agent such as silicone oil, fluorinated polyolefin (see Patent Document 1) that significantly reduces the surface tension is added to have sufficient leveling (smoothness), but the recoatability (re-coating property) is insufficient. That is, when the hard coating contains such a leveling agent that reduces the surface tension, when other composition layers corresponding to the purpose, such as an antistatic layer, a high refractive index layer, a low refractive index layer, etc., are coated on the hard coating in order to reduce the surface energy of the hard coating, coating defects such as coating depression, uneven coating, and coating streaks often occur, and the requirements in terms of recoating property cannot be fully met.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2002-267804 Summary of the invention
[0008] Problems to be solved by the invention
[0009] The present invention aims to solve at least one of the problems in the above-mentioned prior art. In particular, the present invention aims to provide a hard coating film having high surface hardness, excellent scratch resistance, and excellent leveling (smoothness) and recoatability (re-coatability).
[0010] Technical means to solve problems
[0011] The inventors of the present invention have conducted intensive studies to solve the above problems and have found that a hard coating film having excellent leveling properties (smoothness) and recoatability (re-coatability) can be provided by making the hard coating layer contain a specific fluorine-containing leveling agent, thereby completing the present invention.
[0012] That is, the present invention is as follows.
[0013] <1> A hard coating film comprising a substrate layer containing a thermoplastic resin and a hard coating layer as a cured coating layer on at least one surface of the substrate layer, wherein:
[0014] The hard coating layer contains a fluorine-containing leveling agent, and the surface roughness of the hard coating layer is less than 10 nm. The fluorine atom concentration F(80°) at an angle of 80° measured by angle-resolved XPS is less than 10 atomic %, and the fluorine atom concentration F(30°) at an angle of 30° is less than 10 atomic %.
[0015] <2> According to the above <1> The hard coating film, wherein the contact angle of the surface of the hard coating layer with propylene glycol monomethyl ether is 10° or less.
[0016] <3> According to the above <1> or <2> The hard coating film, wherein the hard coating layer further contains a photopolymerization initiator, polyurethane (meth) acrylate and solid inorganic particles.
[0017] <4> According to the above <1> ~ <3> The hard coating film according to any one of the preceding claims, wherein the pencil hardness of the surface of the hard coating layer is H or higher.
[0018] <5> According to the above <1> ~ <4> The hard coat film described in any one of the above has, on the surface of the hard coat layer, a low refractive index layer having a refractive index lower by 0.05 or more than that of the hard coat layer.
[0019] <6> According to the above <5> In the hard coating film, the low refractive index layer contains a fluorine-containing leveling agent and a silicon-containing slip agent.
[0020] <7> According to the above <1> ~ <6> The hard coating film described above is used for insert molding.
[0021] <8> A resin molded product having the above <1> ~ <7> The hard coating film described above.
[0022] Effects of the Invention
[0023] According to the present invention, a hard coating film having high surface hardness, excellent scratch resistance, and excellent leveling (smoothness) and recoatability (re-coatability) is provided. According to the present invention, the coating property of the functional material provided on the hard coating layer is improved, so that it can be applied to multi-layer applications such as anti-reflection films for displays having hard coating functions. DETAILED DESCRIPTION
[0024] The present invention will be described in detail below. However, the present invention is not limited to the following embodiments, and can be arbitrarily modified within the scope of the effects of the present invention.
[0025] [Hard Coat]
[0026] One embodiment of the present invention is a hard coating film having a base layer containing a thermoplastic resin and a hard coating layer as a cured coating layer on at least one surface of the base layer. The hard coating layer improves the surface hardness and scratch resistance of the hard coating film.
[0027] Hereinafter, each layer member included in the hard coat film as such a laminate will be described.
[0028] [Hard coating]
[0029] The hard coating layer of the present invention contains a fluorine-containing leveling agent, and the surface roughness of the hard coating layer is 10 nm or less, preferably 9.6 nm or less, and more preferably 8.0 nm or less. In the present invention, the surface roughness is a value measured by the method described in the examples described below.
[0030] In addition, in the hard coating layer of the present invention, the fluorine atom concentration F(80°) at an angle of 80° measured by angle-resolved XPS is 10 atom% or less, preferably 8 atom% or less, and more preferably 5 atom% or less. On the other hand, the fluorine atom concentration F(30°) at an angle of 30° measured by angle-resolved XPS is 10 atom% or less, preferably 9 atom% or less, and more preferably 7 atom% or less. In the present invention, the fluorine atom concentration F is a value measured by the method described in the examples described later.
[0031] The present invention is characterized in that a fluorine-containing leveling agent is used in the hard coat layer in order to reduce the surface tension of the coating film and reduce coating unevenness.
[0032] "Leveling" refers to the property of the paint to flow and form a flat and smooth coating film after coating. If there are few microscopic fluctuations such as brush marks, orange peel (the texture of orange peel) and ripples on the surface of the coating film, the leveling property is judged to be good.
[0033] In a hard coating film using a conventional fluorine-containing leveling agent, fluorine atoms are segregated on the surface of the hard coating layer due to high smoothness, making it difficult to achieve both good appearance and recoatability. Therefore, the inventors of the present invention eliminated the segregation of fluorine atoms on the surface by using a fluorine-containing leveling agent that is not easily segregated on the surface of the hard coating layer, thereby providing a hard coating film with good appearance and excellent recoatability (less coating depression).
[0034] There are no particular restrictions on the fluorine-containing leveling agent used in the hard coating layer of the present invention, as long as the above-mentioned leveling property (smoothness) and recoatability (re-applicability) can be achieved. Preferably, FUTAGENT 602A (a surfactant having a perfluoroolefin group, a UV reactive group and a lipophilic group (organic component) produced by NEOS COMPANY LIMITED), FUTAGENT 218 (produced by NEOS COMPANY LIMITED), FUTAGENT 683 (produced by NEOS COMPANY LIMITED), MEGAFACE R-40 (produced by DIC Corporation) and the like are used.
[0035] In the present invention, when the content of the polyurethane (meth)acrylate preferably used as a coating material for forming the hard coat layer is taken as 100 mass %, the content of the fluorine-containing leveling agent is preferably from 0.01 mass % to 1 mass %, and more preferably from 0.05 mass % to 0.5 mass %.
[0036] In one embodiment of the present invention, preferably, the hard coat layer has a low refractive index layer and / or a high refractive index layer described later, and in a hard coat film having a laminate structure comprising a low refractive index layer, a high refractive index layer and a hard coat layer, preferably, the hard coat layer is laminated between the substrate layer and the high refractive index layer. That is, preferably, these laminates are laminated in the order of the substrate layer, the hard coat layer, the high refractive index layer and the low refractive index layer.
[0037] In the hard coating film having such a laminate structure, not only a good antireflection effect can be achieved, but also the surface hardness, that is, the hardness of the surface opposite to the base layer is improved.
[0038] The hard coat layer is preferably formed by hard coating treatment on the surface of the substrate layer, etc. That is, it is preferred to laminate the hard coat layer by applying a hard coating material that is heat-curable or curable by active energy rays and then curing it.
[0039] As an example of a coating material cured by active energy rays, there can be cited a resin composition comprising one or more monofunctional or polyfunctional acrylate monomers or oligomers, and more preferably a resin composition comprising a polyurethane (meth)acrylate oligomer. In this specification, "(meth)acrylate" refers to acrylate and methacrylate.
[0040] These resin compositions contain the above-mentioned fluorine-containing leveling agent as an essential component, and preferably contain a photopolymerization initiator and solid inorganic particles as a curing catalyst.
[0041] In addition, as thermosetting resin coatings, polyorganosiloxane-based coatings, cross-linked acrylate-based coatings, etc. This resin composition not containing a fluorine-containing leveling agent is also commercially available as a hard coating agent for acrylic resin or polycarbonate resin, and can be appropriately selected in consideration of the applicability to the coating production line.
[0042] In addition to the organic solvent, various stabilizers such as ultraviolet absorbers, light stabilizers, antioxidants, defoamers, thickeners, antistatic agents, antifogging agents, surfactants, etc. may be appropriately added to these coatings as needed.
[0043] As an example of a hard coating material cured by active energy rays, there can be mentioned a coating material in which 1 to 10 parts by mass of a photopolymerization initiator is added to 100 parts by mass of a photopolymerizable resin composition prepared by mixing 40 to 95 parts by mass of a hexafunctional urethane acrylate oligomer and 5 to 60 parts by mass of a (meth)acrylate such as 2-(2-vinyloxyethoxy)ethyl (meth)acrylate [2-(2-vinyloxyethoxy)ethyl acrylate: VEEA)].
[0044] As the photopolymerization initiator, a commonly used known photopolymerization initiator can be used, and specific examples thereof include benzoin, benzophenone, benzoin ethyl ether, benzoin isopropyl ether, 2,2-dimethoxy-2-acetophenone, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, azobisisobutyronitrile, and benzoyl peroxide.
[0045] In addition, the solid inorganic particles are not particularly limited as long as they can improve the scratch resistance of the hard coating layer, and preferably nano-silica particles, nano-alumina particles, nano-zirconia particles, glass particles, etc. are used, and nano-silica particles are more preferably used.
[0046] In the present invention, when the content of the polyurethane (meth)acrylate preferably used as a coating material for forming the hard coat layer is taken as 100 mass %, the content of the solid inorganic particles is preferably 0.5 mass % to 3 mass %, and more preferably 1.0 mass % to 2.0 mass %.
[0047] The refractive index of the hard coat layer is preferably about the same as that of the substrate layer. Specifically, the hard coat layer preferably has a refractive index in the range of 1.43 to 1.65. The refractive index of the hard coat layer is more preferably 1.47 to 1.60, and even more preferably 1.49 to 1.57.
[0048] Furthermore, the difference between the refractive index of the base layer and the refractive index of the hard coat layer is preferably 0.04 or less, more preferably 0.03 or less, and even more preferably 0.02 or less.
[0049] In order to make the refractive index of the hard coat layer close to the refractive index of the substrate layer, a high refractive index material described below may be appropriately added to the hard coat paint.
[0050] The thickness of the hard coat layer is not particularly limited, but is preferably 1 to 10 μm, more preferably 2 to 8 μm, and even more preferably 2 to 6 μm.
[0051] In order to improve the surface state, when a second cured layer is further formed on the first cured layer containing the above-mentioned fluorine-containing leveling agent, the leveling agent present on the surface of the first cured layer is sometimes blocked at the interface between the first cured layer and the second cured layer, and a structure that connects the first cured layer and the second cured layer cannot be formed, thereby causing the problem of poor adhesion. In addition, when the wettability of the first cured layer is low, sometimes a depression occurs when the second cured layer is applied, and the second cured layer cannot be formed. Therefore, it is necessary to select an appropriate leveling agent that can solve these problems.
[0052] Furthermore, when the first cured layer is not completely cured, the leveling agent may be extracted by the second cured layer forming liquid and seep out on the second cured layer when forming the second cured layer, thereby possibly affecting the performance of the surface of the second cured layer.
[0053] [Base material layer]
[0054] The substrate layer included in the hard coating film contains a thermoplastic resin. The type of thermoplastic resin is not particularly limited, and various resins such as polycarbonate (PC) resin, acrylic resin such as polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), triacetyl cellulose (TAC), polyethylene naphthalate (PEN), polyimide (PI), cycloolefin copolymer (COC), norbornene-containing resin, polyether sulfone, cellophane, aromatic polyamide, etc. can be used. The thermoplastic resin of the substrate layer preferably includes at least polycarbonate resin among these options.
[0055] The type of polycarbonate resin contained in the substrate layer is not particularly limited, as long as it is a resin containing a -[O-R-OCO]- unit containing a carbonate bond in the main chain of the molecule (R is an aliphatic group, an aromatic group, or a group containing both an aliphatic group and an aromatic group, and further has a linear structure or a branched structure). Preferably, the polycarbonate has a bisphenol skeleton, and particularly preferably a polycarbonate having a bisphenol A skeleton or a bisphenol C skeleton. As the polycarbonate resin, a mixture or copolymer of bisphenol A and bisphenol C can be used. By using a bisphenol C-based polycarbonate resin, such as a polycarbonate resin consisting only of bisphenol C, a mixture or copolymer of bisphenol C and bisphenol A, the hardness of the substrate layer can be increased.
[0056] The viscosity average molecular weight of the polycarbonate resin is preferably 15,000 to 40,000, more preferably 20,000 to 35,000, and even more preferably 22,500 to 25,000.
[0057] In addition, as the acrylic resin contained in the substrate layer, there is no particular limitation, and examples thereof include homopolymers of various (meth) acrylic esters represented by polymethyl methacrylate (PMMA) and methyl methacrylate (MMA), or copolymers of PMMA or MMA with more than one other monomer, and mixtures of various mixtures of these resins. As monomer examples, cyclic anhydride units, N-substituted maleimide units, aromatic vinyl compound units, aliphatic vinyl compound units, etc. can be cited. Among them, (meth) acrylic esters containing cyclic alkyl structures with low birefringence, low hygroscopicity, and excellent heat resistance are preferred. As examples of (meth) acrylic resins as described above, there are Acrypet (produced by Mitsubishi Rayon Co., Ltd.), Delpet (produced by Asahi Kasei Chemical Co., Ltd.), and Parapet (produced by KURARAY CO., LTD.), but are not limited to these.
[0058] Among them, the use of a mixture containing a polycarbonate resin and the above-mentioned acrylic resin is preferred because the hardness of the substrate layer, particularly the surface layer (the layer on the hard coat layer side) of the substrate layer forming the laminate can be increased.
[0059] In addition, the substrate layer may also contain additives as components other than the thermoplastic resin. For example, there are at least one additive selected from the group consisting of a heat stabilizer, an antioxidant, a flame retardant, a flame retardant aid, an ultraviolet absorber, a release agent, and a colorant. In addition, an antistatic agent, a fluorescent brightener, an antifogging agent, a fluidity improver, a plasticizer, a dispersant, an antibacterial agent, etc. may also be added to the substrate layer.
[0060] The base material layer preferably contains 80% by mass or more of thermoplastic resin, more preferably 90% by mass or more, and particularly preferably 95% by mass or more of thermoplastic resin. In addition, the base material layer preferably contains 50% by mass or more of polycarbonate resin, more preferably 70% by mass or more, and particularly preferably 75% by mass or more of polycarbonate resin in the thermoplastic resin.
[0061] The base material layer preferably has a refractive index in the range of 1.49 to 1.65. The refractive index of the base material layer is more preferably about 1.49 to 1.60.
[0062] The thickness of the substrate layer is not particularly limited, but is preferably 30 to 1000 μm (1 mm), more preferably 50 to 700 μm, and particularly preferably 100 to 500 μm. In addition, two or more substrate layers may be provided in the hard coat film, and when multiple substrate layers are provided, the total thickness of the substrate layers is, for example, 100 to 1000 μm, preferably about 200 to 500 μm.
[0063] As the substrate layer including multiple layers, i.e., the substrate layer as a laminated body, the following structures can be cited, for example. A laminated body in which an acrylic resin layer such as the acrylic resin such as poly(methyl meth)acrylate resin (PMMA: polymethyl acrylate and / or polymethyl methacrylate) is laminated as a surface layer (layer on the side of the hard coating layer) on a layer of the polycarbonate resin (PC) such as bisphenol A; a laminated body in which a resin layer formed by a copolymer of the PMMA and one or more other monomers is laminated; a laminated body in which a polycarbonate resin (PC) such as bisphenol C is laminated on a polycarbonate resin (PC) layer such as bisphenol A, etc. In a laminated body in which a polycarbonate resin (PC) layer containing bisphenol A and a polycarbonate resin (PC) layer containing bisphenol C are laminated, for example, a polycarbonate resin layer containing bisphenol C is used as a surface layer.
[0064] Furthermore, as the surface layer, it is preferable to use a layer having high hardness, particularly a layer having a higher hardness than other base material layers.
[0065] As the polycarbonate resin of the thermoplastic resin used in the laminate, the above-mentioned resin is also suitable for use, as is the polycarbonate resin forming the monolayer substrate layer. For example, a mixture or copolymer of bisphenol A and bisphenol C can be used. By using bisphenol C-based polycarbonate resins, for example, polycarbonate resins only of bisphenol C, polycarbonate resins of a mixture or copolymer of bisphenol C and bisphenol A, it is confirmed that the effect of the hardness of the surface layer (layer on the hard coating side) as the substrate layer of the laminate can be particularly improved. And, in order to further improve the hardness, a mixture of the above-mentioned acrylic resin added to a polycarbonate resin, for example, a bisphenol C-based polycarbonate resin can be used.
[0066] [Low refractive index layer (anti-reflection layer)]
[0067] As described above, in the present invention, it is preferred to have a low refractive index layer on the hard coating layer. As the low refractive index layer, it is preferred to have a refractive index that is 0.05 or more lower than the refractive index of the hard coating layer, more preferably 0.07 or more lower, and particularly preferably 0.08 to 0.12 lower. When having a refractive index that is 0.05 or more lower than the refractive index of the hard coating layer, sufficient anti-reflection performance can be obtained, and thus it is preferred.
[0068] The refractive index of the low refractive index layer is preferably in the range of 1.35 to 1.44, more preferably in the range of 1.38 to 1.42, and particularly preferably in the range of 1.39 to 1.41. When the refractive index is less than 1.35, it is sometimes difficult to obtain sufficient hardness, and when the refractive index exceeds 1.44, it is sometimes difficult to obtain sufficient antireflection performance.
[0069] The thickness of the low refractive index layer is preferably 70 to 130 nm, more preferably 80 to 120 nm, and particularly preferably 90 to 110 nm. When the thickness of the low refractive index layer is less than 70 nm, the wavelength region of the light that can prevent reflection changes significantly toward the low wavelength side, and the visual reflectivity deteriorates; and when the thickness exceeds 130 nm, the wavelength region of the light that can prevent reflection changes significantly toward the high wavelength side, and the visual reflectivity deteriorates.
[0070] The low refractive index layer is preferably disposed on the outermost side of the hard coat film in order to suppress reflection of the hard coat film.
[0071] The low refractive index layer is formed by applying a coating solution consisting of a low refractive index layer forming composition on the hard coat layer, and then curing by ultraviolet irradiation. The coating method, curing conditions, and viscosity adjustment diluent solvent are not particularly limited and can be appropriately selected. The low refractive index layer forming composition can contain, for example, an ultraviolet curable resin, a fluorine-containing leveling agent, a silicon-containing slip agent, hollow silica particles, and a photopolymerization initiator.
[0072] <Ultraviolet curing resin>
[0073] As the ultraviolet curable resin forming the low refractive index layer, if it is a multifunctional (meth)acrylate, its type is not particularly limited. As the resin forming the low refractive index layer in this type of film, in addition to the multifunctional (meth)acrylate, a resin using a reactive silicon compound such as γ-acryloxypropyltrimethoxysilane as a starting material can also be used, but from the perspective of both productivity and hardness, a composition containing an ultraviolet curable multifunctional (meth)acrylate as a main component is preferred.
[0074] The polyfunctional (meth)acrylate is not particularly limited, and examples thereof include (meth)acrylic acid derivatives of polyfunctional alcohols such as dipentaerythritol hexa(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, tetramethylolmethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and 1,6-bis(3-(meth)acryloyloxy-2-hydroxypropoxy)hexane, as well as polyethylene glycol di(meth)acrylate and polyurethane (meth)acrylate. In the present invention, polyurethane (meth)acrylate is particularly preferably used.
[0075] In addition, multifunctional (meth) acrylate can also be a fluorine-containing monomer. The fluorine-containing monomer having a structure in which fluorine atoms are introduced into the molecule in the form of fluoromethylene or fluoromethine is a monomer in which almost all fluorine atoms are introduced into the molecule in the form of fluoromethylene or fluoromethine. As long as it is a multifunctional monomer, all known monomers can be used. That is, it can be any one of more than two (multifunctional) monomers, or it can be a mixture thereof. These fluorine-containing compounds can improve the strength and hardness of the cured film, and can improve the scratch resistance and wear resistance of the cured film surface. Among the fluorine-containing compounds, from the perspective of being able to form a cross-linked structure, the strength of the cured film and the high hardness, preferably fluorine-containing multifunctional (meth) acrylate.
[0076] <Fluorinated leveling agent>
[0077] The fluorine-containing leveling agent contained in the low refractive index layer can impart smoothness and fingerprint erasability to the layer, and can reduce the adhesion of fingerprints as lipids that adhere to the surface of the low refractive index layer after touching it, thereby improving the fingerprint erasability.
[0078] As the fluorine-containing leveling agent contained in the low refractive index layer, preferably, a (meth)acrylate containing a C2 to C7 perfluoroalkyl chain is used, and specifically, Optool DAC-HP manufactured by Daikin Industries, Ltd., or MEGAFACE RS-75 and RS-78 manufactured by DIC Corporation are used.
[0079] The fluorine-containing leveling agent is preferably contained in the composition for forming the low refractive index layer in an amount of 1 to 20% by mass, more preferably 2.5 to 10% by mass. When the content is less than 1% by mass, the adhesion of fingerprints adhered to the surface of the low refractive index layer may not be reduced; and when the content exceeds 20% by mass, it is sometimes difficult to obtain sufficient hardness and anti-reflection performance.
[0080] <Silicon-containing lubricant>
[0081] The silicon-containing slip agent contained in the low refractive index layer can impart resistance to cloth scratching. The slip agent is an additive used to ensure the physical stability of the material by preventing adhesion to the metal surface, preventing adhesion between materials, improving the fluidity of the material, and reducing friction within the material or with the metal surface during the thermoforming process of the thermoplastic resin.
[0082] As the silicon-containing slip agent used in the present invention, polydimethylsiloxane is preferred, and polyether-modified polydimethylsiloxane having an acrylic group or polyester-modified polydimethylsiloxane having an acrylic group is more preferred. Specifically, BYK-UV3500, BYK-UV3530, BYK-UV3570, etc. produced by BYK Japan are preferred.
[0083] The silicon-containing slip agent is preferably contained in the composition for forming the low refractive index layer in an amount of 5 to 20% by mass, more preferably 10 to 17.5% by mass. When the content is less than 5% by mass, the resistance to cloth scratching may be insufficient, while when the content exceeds 20% by mass, it may be difficult to obtain sufficient hardness or anti-reflection performance.
[0084] In the present invention, the mass ratio of the silicon-containing slip agent to the fluorine-containing leveling agent contained in the low refractive index layer is preferably 9:1 to 5:5, more preferably 7:1 to 5:5. When the mass ratio of the silicon-containing slip agent is greater than 9:1, it is sometimes difficult to obtain sufficient fingerprint erasability; and when the mass ratio of the fluorine-containing leveling agent is greater than 5:5, it is sometimes difficult to obtain sufficient cloth scratch resistance.
[0085] <Hollow Silica>
[0086] In the low refractive index layer of the present invention, in order to reduce the refractive index of the low refractive index layer, it is preferred to contain hollow silica particles. Hollow silica particles are particles formed of silicon dioxide (silica, SiO2) in a nearly spherical shape and having a hollow portion in its shell. Its average particle size is 10 to 100nm, the shell thickness is about 1 to 60nm, the porosity of the hollow portion is 40 to 45%, and the refractive index is as low as 1.20 to 1.29. Since the hollow portion contains air with a refractive index of 1.0, the cured film formed by curing the multifunctional (meth) acrylate can achieve low refractive index and low reflectivity, and it is also possible to use inorganic particles such as silica particles to improve the scratch resistance and wear resistance of the cured film.
[0087] When the porosity of the hollow portion is less than 40%, the amount of air in the hollow portion is reduced, and sometimes the low refractive index and low reflectivity of the cured film cannot be achieved; and when the porosity of the hollow portion exceeds 45%, in order to increase the porosity, the shell needs to be thinned, and its manufacturing becomes difficult.
[0088] In addition, the hollow silica particles are preferably modified by silane coupling agents as required. Thus, it is possible to show excellent effects that existing conventional (unmodified) silica particles or hollow silica particles do not have, that is, it is possible to show excellent compatibility with multifunctional (meth) acrylates. Therefore, when the modified hollow silica particles are mixed with multifunctional (meth) acrylates, it is possible to suppress the aggregation of the modified hollow silica particles, thereby obtaining a cured film with excellent transparency without whitening. And in the cured film, the polymerizable double bonds of the silane coupling agent and the polymerizable double bonds of the multifunctional (meth) acrylates are copolymerized (chemically bonded) to form a firm cured film, so the scratch resistance and wear resistance of the cured film can be significantly improved.
[0089] The mass ratio of the hollow silica contained in the low refractive index layer to the resin material (the low refractive index coating in Example 5 described later) is preferably 20:80 to 60:40, and more preferably 30:70 to 50:50. Once the amount of hollow silica particles added increases, the surface irregularities increase, and sometimes it is difficult to balance the erasability of fingerprints and the resistance to cloth scratches. This is because fingerprints are easily spread and particles are easy to fall off.
[0090] <Other ingredients>
[0091] In order to reduce the refractive index of the low refractive index layer, the low refractive index layer may contain metal fluoride particles, etc. When metal fluoride particles are used, the metal fluoride contained in the particles may include magnesium fluoride, aluminum fluoride, calcium fluoride, lithium fluoride, etc. The metal fluoride particles are preferably in a granular state, and the particle size (diameter) thereof is not particularly limited, for example, 10 to 200 nm, preferably 30 to 100 nm, more preferably 35 to 80 nm, and particularly preferably 45 to 65 nm.
[0092] Furthermore, in order to improve the scratch resistance, metal oxide fine particles (silicon dioxide, etc.) may be contained.
[0093] The low refractive index layer-forming composition for forming the low refractive index layer preferably contains a photoinitiator (photopolymerization initiator). In addition, the low refractive index layer-forming composition may contain a solvent.
[0094] [High refractive index layer (anti-reflection layer)]
[0095] In order to further reduce the reflectivity, the hard coat film of the present invention preferably has a high refractive index layer between the low refractive index layer and the hard coat layer. The high refractive index layer has a refractive index higher than that of the substrate layer and has an antireflection function similar to the low refractive index layer.
[0096] The high refractive index layer preferably contains a polymer of a resin material including polyurethane (meth) acrylate and (meth) acrylate derived from fluorene diol, isocyanate and (meth) acrylate. That is, the high refractive index layer is preferably a mixture of polyurethane (meth) acrylate and (meth) acrylate obtained by dehydration condensation reaction of at least three components of fluorene diol, isocyanate and (meth) acrylate.
[0097] In the above resin material, the ratio of urethane (meth)acrylate to (meth)acrylate is preferably 99:1 to 50:50 (weight ratio), more preferably 95:5 to 70:30, further preferably 93:7 to 80:20, and particularly preferably 90:10 to 85:15.
[0098] The refractive index of the high refractive index layer is higher than that of the base material layer, and the refractive index of the high refractive index layer is preferably about 1.68 to 1.75, more preferably about 1.69 to 1.74, and even more preferably about 1.70 to 1.73.
[0099] In addition, the difference between the refractive index of the high refractive index layer and the refractive index of the substrate layer is preferably at least 0.09, more preferably at least 0.12, further preferably at least 0.15, and particularly preferably at least 0.17. In addition, the range of the difference between the refractive index of the high refractive index layer and the refractive index of the substrate layer is, for example, 0.03 to 0.70, preferably 0.10 to 0.50, and more preferably 0.15 to 0.26. In this way, by increasing the difference between the refractive index of the high refractive index layer and the refractive index of the substrate layer, the reflectivity of the surface on the high refractive index layer side of the hard coat film can be increased.
[0100] <High refractive index materials>
[0101] The high refractive index layer preferably contains a high refractive index material. The high refractive index material is added to increase the refractive index of the high refractive index layer. That is, by using a high refractive index material to form a high refractive index layer, the refractive index difference between the high refractive index layer and the substrate layer can be increased, further reducing the reflectivity of the hard coating.
[0102] As high refractive index materials, for example, titanium oxide, zirconium oxide (ZrO2), zinc oxide, aluminum oxide, colloidal aluminum oxide, lead titanate, red lead, chrome yellow, zinc yellow, chromium oxide, iron oxide, black iron, copper oxide, magnesium oxide, magnesium hydroxide, strontium titanate, yttrium oxide, hafnium oxide, niobium oxide, tantalum oxide (Ta2O5), barium oxide, indium oxide, europium oxide, lanthanum oxide, zircon, tin oxide and lead oxide, as well as their composite oxides such as lithium niobate, potassium niobate, lithium tantalate and aluminum / magnesium oxide (MgAl2O4), etc.
[0103] In addition, as a high refractive index material, rare earth oxides can be used, for example, scandium oxide, yttrium oxide, lanthanum oxide, cerium oxide, praseodymium oxide, neodymium oxide, samarium oxide, europium oxide, gadolinium oxide, terbium oxide, dysprosium oxide, holmium oxide, erbium oxide, thulium oxide, ytterbium oxide, lutetium oxide, etc. can be used.
[0104] Among the above-mentioned options, zircon (zirconium oxide) is preferred as a high refractive index material.
[0105] The high refractive index material is preferably a granular material. The particle size (diameter) of the granular high refractive index material is not particularly limited, and is, for example, 1 to 100 nm, preferably 5 to 50 nm, more preferably 7.5 to 30 nm, and particularly preferably 10 to 25 nm.
[0106] In addition, for example, the granular high refractive index material preferably includes a coating of an organic layer as a surface treatment layer of the outer surface of the coated metal oxide, etc. The coating of the organic layer improves the compatibility of the high refractive index material with the resin material forming the high refractive index layer, and the high refractive index material and the resin material can be firmly combined.
[0107] As the surface treatment layer, a coating of an organic layer having an ultraviolet-reactive (curable) functional group introduced into the surface is preferred.
[0108] The high refractive index layer preferably contains the resin material and the high refractive index material at a weight ratio of 10:90 to 40:60, and the ratio of the resin material to the high refractive index material is more preferably 15:85 to 35:65, and further preferably 20:80 to 30:70.
[0109] The thickness of the high refractive index layer is not particularly limited, but is preferably 10 to 300 nm, more preferably 30 to 250 nm, further preferably 80 to 200 nm, and particularly preferably 130 to 170 nm.
[0110] <Other ingredients>
[0111] The high refractive index layer or the resin material forming the high refractive index layer preferably contains at least one of a photopolymerization initiator and a leveling agent, and particularly preferably contains a photopolymerization initiator. In addition, the resin material may also contain a solvent. In addition, as examples of leveling agents, fluorine-based leveling agents, acrylic leveling agents, and silicone-based leveling agents can be cited.
[0112] [Other layers]
[0113] In the present invention, in addition to providing a low refractive index layer or a high refractive index layer on the hard coating layer by a wet coating method, the following functional layers may also be provided. As examples, metal layers and / or metal oxide layers, adhesive layers and / or bonding layers, water- and oil-repellent layers, antistatic layers, AG patterns, and other layers and decorative layers that improve visibility may be cited by evaporation or sputtering.
[0114] [Other properties of hard coating]
[0115] <Reflectivity (visual reflectivity)>
[0116] The visual reflectance of the surface on the low refractive index layer side of the hard coat film as one of the preferred embodiments of the present invention is preferably 3.0% or less, more preferably 1.6 to 2.8%, and particularly preferably 1.6 to 2.5%, as measured in accordance with JIS Z 8701. In the present invention, the visual reflectance can be measured by the method described in the Examples described below.
[0117] <Resistance to fabric scratches>
[0118] The surface of the low refractive index layer side of the hard coating film as one of the preferred embodiments of the present invention is preferably excellent in resistance to cloth scratching. Specifically, a 100 g / cm 2 The hard coating film according to one preferred embodiment of the present invention is reciprocated 100 times with a load of , preferably without causing visible scratches.
[0119] <Fingerprint erasability>
[0120] The surface of the low refractive index layer side of the hard coating film as one of the preferred embodiments of the present invention is preferably excellent in fingerprint erasability. Specifically, it is preferred that the fingerprint can be completely erased within 5 times when the test described in the Examples described below is performed.
[0121] [Method for producing hard coating film]
[0122] When manufacturing a hard coating, it is preferred to first form a substrate layer. When manufacturing a substrate layer, materials such as a resin composition are processed into a layer (sheet) according to an existing method. Methods such as extrusion molding and casting molding are used. As an example of extrusion molding, it can be cited that after the pellets, flakes or powder of the resin composition are melt-kneaded by an extruder, they are extruded from a T-die, etc., and the semi-molten sheet obtained by clamping and squeezing with rollers is cooled and solidified to form a sheet.
[0123] Then, a resin material is applied to the outer surface of the single or multiple base layers and cured to form a hard coat layer and a low refractive index layer. As a method for curing the resin material, a method such as photocuring and heat curing can be used.
[0124] [Resin molded products]
[0125] Another embodiment of the present invention is a resin molded product having the above-mentioned hard coating film on the surface. The resin molded product of the present invention can be obtained by, for example, molding the resin by an insert molding melting method and integrating the hard coating film on the surface of the resin molded product. For example, the hard coating film is retained in the cavity of the injection molding mold, and the molten resin is injected into the mold, thereby obtaining a resin molded product with the hard coating film integrated with the surface.
[0126] Examples of the resin molded products include films adhered to the surfaces of computer screens, television screens, plasma display panels, etc., and films used on the surfaces of polarizing plates for liquid crystal display devices, sunglass lenses, prescription glasses lenses, camera viewfinder lenses, various instrument covers, automobile glass, tram glass, vehicle display panels, or electronic equipment housings.
[0127] Example
[0128] The present invention will be described in more detail below with reference to the following examples, but the present invention is not limited to the following examples, and any modifications can be made without departing from the gist of the present invention.
[0129] [Example 1]
[0130] As a substrate, a transparent substrate layer (DF02U manufactured by MGC Filschuster Co., Ltd., total thickness 254 μm) in which a methacrylic resin layer was laminated on a polycarbonate resin layer made of 2,2-bis(4-hydroxyphenyl)propane (bisphenol A) was used. The refractive index of the transparent substrate layer was measured by the method described below and the refractive index was 1.498.
[0131] To 100% by mass of polyurethane acrylate UN-954 (produced by Negami Industries Co., Ltd.), 5% by mass of 1-hydroxy-cyclohexyl-phenyl-ketone (Omnirad-184 produced by IGM RESINS) as a photopolymerization initiator, 2% by mass of nano-silica particles NanoBYK-3650 (produced by BYK Japan), and 0.1% by mass of FUTAGENT602A (produced by NEOS COMPANY LIMITED, a surfactant having a perfluoroolefin group, a UV reactive group and a lipophilic group (organic component)) as a fluorine-containing leveling agent were added, and a solvent (propylene glycol monomethyl ether) was mixed to adjust the concentration to a solid content of 25% by mass to prepare a hard coating A-1.
[0132] In order to form a hard coat layer, the hard coat coating A-1 was applied to the transparent substrate layer using a bar coater to a dry film thickness of 3 μm, and dried in a drying oven at 80°C for 2 minutes. The layer was then irradiated with ultraviolet light using an ultraviolet irradiation device to a cumulative light intensity of 200 mJ / cm 2The hard coating film B-1 was obtained. The refractive index of the hard coating layer of the obtained hard coating film B-1 was measured by the method described below and the refractive index was 1.501.
[0133] [Example 2]
[0134] A hard coating film B-2 was obtained in the same manner as in Example 1 except that the hard coating coating A-2 was used in which the fluorine-containing leveling agent in the hard coating coating A-1 was changed to FUTAGENT 218 (produced by NEOS COMPANY LIMITED).
[0135] [Example 3]
[0136] A hard coating film B-3 was obtained in the same manner as in Example 1 except that the urethane acrylate in the hard coating A-1 was changed to KRM8296 (manufactured by Daicel Allnex Ltd.) and the hard coating A-3 was used and the nano silica particles NanoBYK-3650 were not added.
[0137] [Example 4]
[0138] A hard coating film B-4 was obtained in the same manner as in Example 1 except that the polyurethane acrylate in the hard coating A-1 was replaced with EBECRYL 8402 (produced by DaicelAllnex Ltd.) and the nanosilica particles NanoBYK-3650 were not added.
[0139] [Comparative Example 1]
[0140] A hard coating film B-5 was obtained in the same manner as in Example 1 except that the hard coating coating A-5 was used in which the fluorine-containing leveling agent in the hard coating coating A-1 was changed to FUTAGENT 681 (produced by NEOS COMPANY LIMITED).
[0141] [Comparative Example 2]
[0142] A hard coating film B-6 was obtained in the same manner as in Example 1 except that the fluorinated leveling agent in the hard coating A-1 was replaced with MEGAFACE RS-75 (manufactured by DIC Corporation, having a perfluoroalkyl group, a UV reactive group and a lipophilic group (organic component)).
[0143] [Comparative Example 3]
[0144] A hard coating film B-7 was obtained in the same manner as in Example 1 except that the hard coating coating A-7 in which the fluorine-containing leveling agent in the hard coating coating A-1 was changed to MEGAFACE RS-56 (produced by DIC Corporation) was used.
[0145] [Comparative Example 4]
[0146] A hard coating film B-8 was obtained in the same manner as in Example 1, except that the polyurethane acrylate in the hard coating A-1 was replaced with KRM8296 (produced by Daicel Allnex Ltd.), the nano silica particles NanoBYK-3650 were not added, and the fluorine-containing leveling agent was replaced with MEGAFACE RS-75 (produced by DIC Corporation).
[0147] [Comparative Example 5]
[0148] A hard coating film B-9 was obtained in the same manner as in Example 1, except that the polyurethane acrylate in the hard coating coating A-1 was changed to EBECRYL 8402 (produced by DaicelAllnex Ltd.), the nano silica particles NanoBYK-3650 were not added, and the fluorine-containing leveling agent was changed to MEGAFACE RS-75 (produced by DIC Corporation).
[0149] The hard coating films of Examples 1 to 4 and Comparative Examples 1 to 5 obtained in this manner were measured as follows.
[0150] <Refractive Index>
[0151] The refractive index value (nD) was measured at 20° C. using a D line with a wavelength of 589 nm using an Abbe refractometer (model: NAR-3T) manufactured by ATAGO CO., LTD. In the solution containing a solvent, the refractive index was directly measured in the state containing the solvent, and the refractive index value of the solution after removing the solvent was calculated based on the measured value and the dilution rate of the solvent.
[0152] <Surface Roughness>
[0153] The surface roughness of the hard coating film was measured under the following conditions using a multi-field mode of a scanning white interference microscope VS1330 manufactured by Hitachi High-Technologies Corporation.
[0154] [Optical conditions]
[0155] Camera: Sony XCL-C30 1 / 3 type
[0156] Lens: Double beam interference objective lens (5 times)
[0157] [Measurement conditions]
[0158] Mode: Wave
[0159] Measuring range (one field of view): 935μm×701μm
[0160] Field of view: 5×5
[0161] Overlap rate: 20%
[0162] Measuring range (full field of view): 3928μm×2946μm
[0163] <Angle-resolved XPS (X-ray Photoelectron Spectroscopy)>
[0164] The measurement was performed using a scanning X-ray photoelectron spectrometer PHI5000 manufactured by ULVAC-PHI, INCORPORATED under the following conditions.
[0165] X-ray source: Al Kα monochromatic 1486.6eV 50W
[0166] Analysis area: 1.0×0.2mm 2
[0167] Measuring angle: 30°, 80°
[0168] Path energy: 23eV (C1s, O1s, F1s)
[0169] 187eV (N1s, Si2p)
[0170] Photoelectron acceptance angle: narrowband mode (±5°)
[0171] Based on the obtained peak area, the surface atomic concentration was calculated using the relative sensitivity factor provided by PHI. Among them, since the concentrations of N1s and Si2p were low, the path energy was reduced for high-sensitivity measurement.
[0172] <Contact Angle (Propylene Glycol Monomethyl Ether)>
[0173] The contact angle was measured using an automatic contact angle meter DMo-601 (manufactured by Kyowa Interface Science Co., Ltd.) under the following conditions using a test liquid of propylene glycol monomethyl ether.
[0174] Liquid volume: 2.0μL
[0175] Analysis method: Θ / 2 method
[0176] <Recoatability (topcoat adaptability)>
[0177] A coating of polyurethane acrylate UN-954 (produced by Negami Industries Co., Ltd.) diluted in propylene glycol monomethyl ether (PGME) at a solid content concentration of 25% by mass was applied to the hard coating layer of each hard coating film using a bar coater to a dry film thickness of 1 μm, and dried in a drying oven at a temperature of 80°C for 2 minutes. At this time, the recoatability was evaluated in three levels according to the number of depressions generated. The evaluation criteria are as follows, and products rated 0 are judged to be qualified for recoatability.
[0178] 0: 0, 1
[0179] △: 2 to 5
[0180] ×: 6 or more
[0181] <Smoothness>
[0182] In order to eliminate the influence of back reflection, the substrate layer side surface of the hard coating film (either side surface in the case of double-sided hard coating) was colored with black marker ink. The uncolored side of the hard coating film was faced upward and visually observed from above under a three-wavelength fluorescent lamp to evaluate smoothness.
[0183] ○ (Good smoothness): There is almost no deformation or unevenness on the surface.
[0184] △ (smoothness is good): Slight deformation or unevenness can be seen on the surface.
[0185] × (poor smoothness): deformation or unevenness is visible on the surface.
[0186] <Pencil Hardness>
[0187] The pencil hardness of the hard coat surface of the hard coat film was evaluated in accordance with JIS K5600-5-4. The pencil hardness was evaluated under a load of 500 g.
[0188]
[0189] [Example 5]
[0190] A curable low-refractive index coating was prepared as follows. First, dry air was passed into a five-necked flask equipped with a stirrer, a thermometer, a cooler, a monomer dropping funnel, and a dry air inlet tube to dry the system. Then, 58.9 parts by mass of 2,2,3,3-tetrafluoro-1,4-butanediol (C4DIOL produced by Exfluor Research Corporation), 279.8 parts by mass of pentaerythritol triacrylate, 0.5 parts by mass of dibutyltin laurate as a polymerization catalyst, and 500 parts by mass of butanone as a solvent were added to the five-necked flask, and the temperature was raised to 60°C. Then, after adding 161.3 parts by mass of isophorone diisocyanate, the reaction was carried out at 60-70°C. The reaction was terminated after confirming that the isocyanate residues in the reactants were completely consumed using infrared absorption spectroscopy to obtain a hexafunctional polyurethane acrylate oligomer.
[0191] Furthermore, 2-(2-vinyloxyethoxy)ethyl acrylate (VEEA) was mixed with the urethane acrylate oligomer (urethane acrylate liquid) at a ratio of urethane acrylate liquid / VEEA=90 / 10 (mass %).
[0192] Hollow silica (Thrulya 4320, manufactured by JGC Catalysts & Chemicals Co., Ltd.) was mixed with the low refractive index coating (liquid component of resin material) obtained as described above at a ratio of hollow silica / resin material = 50 / 50 (mass %). 4 mass % of 1-hydroxy-cyclohexyl-phenyl ketone (Omnirad-184 manufactured by IGM RESINS) as a photopolymerization initiator, 10 mass % of BYK-UV3500 (manufactured by BYK Japan) as a silicon-containing slip agent, and 10 mass % of RS-78 (manufactured by DIC) as a fluorine-containing leveling agent were dissolved, and a solvent (propylene glycol monomethyl ether) was added to adjust the concentration so that the solid content concentration was 3 mass %. The obtained low refractive index coating was referred to as low refractive index coating C-1.
[0193] The low refractive index coating C-1 was applied on the hard coating layer of the hard coating film B-1 described in Example 1 to a dry coating film thickness of 100 nm, and dried at 80°C for 2 minutes. The film was then irradiated with ultraviolet light using an ultraviolet curing device to a cumulative light intensity of 400 mJ / cm 2 The low refractive index coating material was cured. Thus, a low refractive index layer having a thickness of 100 nm was formed on the outer surface of the hard coating film B-1, thereby producing an antireflection film D-1.
[0194] [Example 6]
[0195] An antireflection film D-2 was produced in the same manner as in Example 5 except that the hard coat film B-2 described in Example 2 was used.
[0196] The antireflection films of Examples 5 and 6 prepared in this manner were measured as follows.
[0197] <Refractive Index>
[0198] The refractive index value (nD) was measured at 20°C using the D line of 589 nm using an Abbe refractometer (model: NAR-3T) manufactured by ATAGO CO., LTD. Among them, in the solution containing a solvent, the refractive index was directly measured in the state containing the solvent, and the refractive index value of the solution after removing the solvent was calculated based on the measured value and the dilution rate of the solvent. As a result, the refractive index of the low refractive index layer in the anti-reflection films D-1 and D-2 was 1.390 and 1.390, respectively.
[0199] <Reflectivity (visual reflectivity)>
[0200] The anti-reflection film was measured using SD7000 manufactured by Nippon Denshoku Industries Co., Ltd. in accordance with JIS Z 8701. In order to prevent reflection from the back side (substrate layer side) of the film of each example, the surface opposite to the low refractive index layer was coated with a black spray and dried before measurement. The results confirmed that the anti-reflection films D-1 and D-2 were both 1.7%, showing sufficient anti-reflection performance.
[0201] <Resistance to fabric scratches>
[0202] 100 g / cm2 was applied to 4-fold medical medi gauze (manufactured by Osaki Medical Co., Ltd.) 2 The surface of the low refractive index layer side of the film of each example was reciprocated 100 times with a load of , and the presence or absence of scratches was visually determined and evaluated according to the following criteria.
[0203] ○: No scratches
[0204] ×: There is more than one scratch
[0205] As a result, it was confirmed that both the antireflection films D-1 and D-2 had no scratches.
[0206] <Fingerprint erasability>
[0207] After dropping artificial fingerprint liquid (oleic acid) on the surface of the sample, use a silicone pad to spread the artificial fingerprint liquid thinly to a diameter of about 11mm. Use 3M Japan Scotch-Brite No.5000 cloth to apply the artificial fingerprint liquid on the sample under a load of 500g. Repeat the above test until it is wiped off. Samples that are completely wiped off within 5 times are evaluated as having good fingerprint wipe-off properties, and those that require more than 6 times are evaluated as having poor fingerprint wipe-off properties.
[0208] As a result, it was confirmed that both antireflection films D-1 and D-2 had good fingerprint erasability after being erased three times.
Claims
1. A hard coating film, characterized in that: The hard coating film comprises a base layer containing a thermoplastic resin and a hard coating layer as a cured coating layer on at least one surface of the base layer. The hard coating layer contains a fluorine-containing leveling agent, the surface roughness of the hard coating layer is less than 10 nm, the fluorine atom concentration F80° at an angle of 80° measured by angle-resolved XPS is less than 10 atomic %, and the fluorine atom concentration F30° at an angle of 30° is less than 10 atomic %.
2. The hard coating film according to claim 1, characterized in that The contact angle of the surface of the hard coating layer with propylene glycol monomethyl ether is 10° or less.
3. The hard coating film according to claim 1 or 2, characterized in that: The hard coating layer further contains a photopolymerization initiator, urethane (meth)acrylate, and solid inorganic particles.
4. The hard coating film according to any one of claims 1 to 3, characterized in that The pencil hardness of the surface of the hard coating layer is H or higher.
5. The hard coating film according to any one of claims 1 to 4, characterized in that A low refractive index layer having a refractive index lower than that of the hard coating layer by 0.05 or more is provided on the surface of the hard coating layer.
6. The hard coating film according to claim 5, characterized in that The low refractive index layer contains a fluorine-containing leveling agent and a silicon-containing slip agent.
7. The hard coating film according to any one of claims 1 to 6, characterized in that The hard coating is used for insert molding applications. 8 . A resin molded article having the hard coating film according to claim 1 on its surface.
Citation Information
Patent Citations
Antireflection film and method for manufacturing the same
JP2002267804A